Measuring Performance, Efficiency of Allied & Muslim Commercial Banks Before after Privatization Period - Bhatti, Nadeem (Journal of Asian Business Strategy, 2012)
This research investigates the comparative analysis of the performance, Efficiency of Allied & Muslim Commercial Bank before and after Privatization period. The primary resource of data for empirical analysis is the balance sheets of target years collected from the different branches of Allied bank and Muslim Commercial Bank in Khairpur and Sukkur. The balance sheets along with the income statements of those banks were also collected. For secondary source, year wise reports from various library sources were collected and studied. The reports from the State Bank of Pakistan were also brought to the analysis to see the comparison and impact of privatization and role of the central bank in the process of privatization. The comparative analysis and efficiency levels were measured by using nonparametric statistical tests, regression analysis, and the Reliability model. The reliability model used for the first time in management sciences research has unique features. The model predicted the life of components of the banking business. The expected success and failure of the indicators before and after privatization are assessed by using the reliability model. In nonparametric statistical tests applied were the Chi-square, Sign Test, Sign rank test and Wilcoxon and Hotelling’s T tests. Means were compared by using t-test.